Effect of extrusion in the elaboration of an animal feed based on Moringa oleifera Lam and Zea mays as a partial substitute of fishmeal in the diet of the adult stage of Oreochromis niloticus - Pérez-Viveros, Karla Jareth; Gutiérrez-Dorado, Roberto; Téllez-Jurado, Alejandro; Gómez- Aldapa, Carlos Alberto; Reyes-Moreno, Cuauhtemoc; Navarro-Cortez, Ricardo Omar; Bautista-Monroy, Suri Sadai; Cadena Ramírez, Arturo (Acta Universitaria, 2019)
The rising demand for fishmeal, as well as the search for sustainable active food, has led to the development of food-based on by-products and the use of vegetable flours, leading to the elimination of poorly consumed and poorly assimilated food from aquaculture. These are the main economic, nutritional and environmental problems in the intensive cultivation of Nile tilapia (Oreochromis niloticus). The amount of fish protein in fish diets is above nutritional requirements. And tilapia does not ingest the food that does not float, leading to over-rationing. This study explores the effect of extrusion on the elaboration of a feed based on Moringa leaf flour (Moringa oleifera Lam) and Zea mays as a partial substitute of fishmeal in the diet of the adult stage of Oreochromis niloticus. The analysis revealed that the combination provides desirable physical properties for the feeding of the fish, and their optimal growth of tilapia because they present a content ideal of protein for the adult stage and characteristics such as the velocity of sinking, density, and hardness.